1992
DOI: 10.1021/np50090a005
|View full text |Cite
|
Sign up to set email alerts
|

Scoparic Acid A, a β-Glucuronidase Inhibitor from Scoparia dulcis

Abstract: The 70% EtOH extract of Scoparia dulcis showed inhibitory activity against beta-glucuronidase from bovine liver. Bioassay-directed fractionation of the active extract led to the isolation of three labdane-type diterpene acids, scoparic acid A [1] [6-benzoyl-12-hydroxy-labda-8(17), 13-dien-18-oic acid], scoparic acid B [2] [6-benzoyl-14,15-dinor-13-oxo-8(17)-labden-18-oic acid], and scoparic acid C [3] [6-benzoyl-15-nor-14-oxo-8(17)-labden-18-oic acid], the structures of which were established by spectral means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 1 publication
1
25
0
Order By: Relevance
“…(Table), were in good agreement with those previously reported for caesalpinista B( 1' ') [ 5].T hese findings indicated that 1 is identical to caesalpinista B. However, the (18 -20) [4] [6] and not for an a-oriented one (28 -29) [7 -9]. These findings suggested that it is necessary to re-examine the configurational assignment as reported for 1' ' [5].A s the 1 H-NMR spectrum of 1 recordedi nC DCl 3 showed partiallyo verlapped signals,1 D-difference NOE experiments were performed in C 6 D 6 .I rradiation of H a ÀC(20) enhanced Me(19)( 6.5%),i ndicating that Me(19)i sa xial and b-oriented.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…(Table), were in good agreement with those previously reported for caesalpinista B( 1' ') [ 5].T hese findings indicated that 1 is identical to caesalpinista B. However, the (18 -20) [4] [6] and not for an a-oriented one (28 -29) [7 -9]. These findings suggested that it is necessary to re-examine the configurational assignment as reported for 1' ' [5].A s the 1 H-NMR spectrum of 1 recordedi nC DCl 3 showed partiallyo verlapped signals,1 D-difference NOE experiments were performed in C 6 D 6 .I rradiation of H a ÀC(20) enhanced Me(19)( 6.5%),i ndicating that Me(19)i sa xial and b-oriented.…”
supporting
confidence: 88%
“…Thes pecific optical rotation, UV,e lectronic circular dichroism( ECD), IR, 1 H-and 13 C-NMR,a nd HR-ESI-FT-MS data of the product were identical to those of 3.T hese results suggested 2 to be an acetyl analog of 1.T his assumption was supported by the NMR data of 2 (Table), which were very similar to those of caesalpinista B(1), exceptfor the presence of an additional Ac group in 2.T he significant downfield shift (þ 1.0) of HÀC(6)i n2 indicatedt hat the additional Ac group is linked to the O-atom at C(6). As the 1 H-NMR spectrum of 2 recordedi nC DCl 3 showed partially overlapped signals, extensive NMR recordings were also performed in C 6 D 6 . The 1 H, 1 H-COSY and HMB correlationss hown in Fig.…”
mentioning
confidence: 99%
“…The plates were read on a multiplate reader (spectra MAX-340) at 405 nm. The inhibitory activities were determined as described previously, 7) except that 5 ml each of test compound was dissolved in DMSO, mixed with enzyme, and incubated at 37°C for 15 min before the addition of substrate to start the reaction. The percentage inhibitory activity was calculated as follows: (EϪS)/Eϫ100, where E is the activity of enzyme without test material and S is the activity of enzyme with test material.…”
Section: Methodsmentioning
confidence: 99%
“…Endogenous biliary bglucuronidase deconjugates the glucuronides of bilirubin and causes the development of cholelithiasis in human bile. 4) Many b-glucuronidase inhibitors such as 8-hydroxytricetin-7-glucuronide and isovitexin, 5) trihydroxy pipecolic acid, 6) and scoparic acid A and C 7) have already been isolated from different plants and some are used clinically.…”
mentioning
confidence: 99%
“…Amelin, a compound with anti-diabetic properties (Nath, 1943) and 6-metoxibenzoxazolinone, a depressor of arterial blood pressure (Chen and Chen, 1976;Kawasaki et al, 1987) have also been identified in this species. Inhibition of ␤-glucuronidase by scoparic acid A (Hayashi et al, 1992) and by 8-hydroxytricetin-7-glucuronide (Kawasaki et al, 1988), antiviral activity by scopadulin (Hayashi et al, 1990a) and scopaducilic acid B Hayashi et al, 1992) have been also reported. Previous studies from our laboratory demonstrated analgesic (Freire et al, 1991) and anti-inflammatory (Freire et al, 1993) activities due to the presence of the triterpene glutinol isolated from its ethanolic crude extract.…”
Section: Introductionmentioning
confidence: 94%